The Impact of Nasal and Sinus Surgery on Obstructive Sleep Apnea. (23rd August 2013) - Friedman, Michael; Pott, Thomas R.; Cipta, Stephanie
Abstract : Objectives: Evaluate the impact of combined endoscopic sinus surgery (ESS) and nasal surgery on the objective measurements of obstructive sleep apnea (OSA) by comparing polysomnography (PSG) data before and after combined ESS and nasal surgery. Design: Retrospective review of medical records. Methods: Fifty‐one OSA patients with chronic sinusitis were identified who underwent combined ESS and nasal surgery as well as pre‐ and postoperative PSG. Clinic charts were reviewed and data collected. Pre‐ and postoperative PSG data were compared to determine whether combined ESS and nasal surgery improved apnea‐hypopnea index (AHI) and oxygen saturation. Results: Postoperative AHI did not change significantly following combined ESS and nasal surgery (P > 0.05). Change in AHI ranged from an increase of 51 events/hr to a decrease of 52.1 events/hr. 43% of patients had an improvement or worsening in postoperative AHI within 5 events/hr, and 80% had a change in AHI within 20 events/hr. There was no significant correlation between preoperative AHI, body mass index (BMI) and change in AHI (p > 0.05). Combined ESS and nasal surgery did not cure any of the patients' OSA. Conclusions: There does not appear to be a significant change in AHI following combined ESS and nasal surgery in patients with chronic sinusitis and OSA. Combined ESS and nasal surgery can lead to an improvement, worsening, or lack of change in AHI. This study showed that BMI and preoperative AHI cannot be used to determine whether combined ESS and nasal surgery will impact their sleep apnea.